Determinants of Diarrhea in Toddlers at Post-Declaration Open-Defecation-Free Area - Siwiendrayanti, Arum; Maulidah, Inda Zumalat Dawil (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Kudus District Health Office in 2020 reported that diarrhea was still the main cause of post-neonatal and toddler mortality even though Kudus District had become an Open Defecation Free (ODF) District in 2019. The highest case finding was in the working area of the Gondosari Health Center at 22.9% in 2020 and an increase of 20.8% compared to the previous year. Aim: to find out the determinants of the incidence diarrhea in toddler after ODF declaration in the work area of the Gondosari Health Center, Kudus Regency. Method: this type of research is an analytic observational study with a cross-sectional design and was obtained in December 2021. The number of samples was 71 samples with the purposive sampling technique. The research instrument used a questionnaire sheet and an observation sheet. Data analysis used Chi-Square and Fisher tests. Result: the results showed the quality of latrine facilities (RP=1.9 and p=0.112), PAMRT (RP=1.0 and p=1,000), PLCRT (RP=3.1 and p=0.001), drinking water sources (RP= 1.1 and p=0.986, water microbiological quality (RP=4.0 and p=0.026). Conclusion: there is a relationship between PLCRT and water microbiological quality with the incidence of diarrhea in children under five after the ODF declaration in the Gondosari Health Center working area. It is hoped that the government will seek a better water source development program for the community and regular monitoring of ODF areas.